The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1038/sj.onc.1208664
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of EGF receptor and c-Src in the survival signals induced by TGF-β1 in hepatocytes

Abstract: Transforming growth factor beta1 (TGF-b1) belongs to a family of polypeptide factors, whose cytostatic and apoptotic functions help restrain the growth of mammalian cells. Although solid data established the role of TGF-b's as suppressor factors in tumorigenic processes, in the context of an advanced stage of disease, TGF-b's could also play a pro-oncogenic role. We have previously shown that TGF-b1 induces both pro-and antiapoptotic signals in foetal rat hepatocytes. In this work, we have focused on its antia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 40 publications
6
153
0
1
Order By: Relevance
“…Furthermore, EGFR is activated and required for TGF-β-induction of antiapoptotic signals, such as AKT [22], constituting a part of the mechanism induced by TGF-β to confer resistance to apoptosis in fetal hepatocytes after an EMT process [37]. Consistent with these data, we see an increased apoptotic index under serum deprivation as well as TGF-β treatment in the presence of AG1478 (Fig.…”
Section: It Is Well Known That Egfr-dependent Signalling Integrates Psupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, EGFR is activated and required for TGF-β-induction of antiapoptotic signals, such as AKT [22], constituting a part of the mechanism induced by TGF-β to confer resistance to apoptosis in fetal hepatocytes after an EMT process [37]. Consistent with these data, we see an increased apoptotic index under serum deprivation as well as TGF-β treatment in the presence of AG1478 (Fig.…”
Section: It Is Well Known That Egfr-dependent Signalling Integrates Psupporting
confidence: 86%
“…A fluorometric assay in the presence of Ac-DEVD-AMC as fluorogenic Caspase-3 substrate was used following a previously described procedure [22].…”
Section: Measurement Of Caspase-3-like Enzymatic Activitymentioning
confidence: 99%
“…Non-Smad, TGF-␤ 1 effectors include MAPKs such as ERK, PI3 kinase, Akt, NADPH oxidase, p21-activated kinase-2, Ras, and Src (5,6,17,19,36,37,50,60). Many of these poorly understood, non-Smad TGF-␤ 1 effects may be indirectly mediated by Smads, but some appear to arise independently of Smads, as illustrated in cells lacking Smads or by mutant TGF-␤ receptors (2,6,50,60).…”
Section: Discussionmentioning
confidence: 99%
“…PI3 kinase phosphorylates the D-3 position of the inositol ring of phosphoinositides, recruiting proteins with pleckstrin homology domains to membranes, such as PKB/kt and PKC-/ . TGF-␤ 1 is reported to stimulate PI3 kinase in mesangial cells (14,30,46) and fibroblasts (6,37,60). We previously reported that primary cultured rat mesangial cells express predominantly PKC-with little or undetectable PKC-.…”
mentioning
confidence: 97%
“…Indeed, ADAM-17 contributes to EGFRligand release and induction of cell proliferation and invasion [137]. A link has been established between TGF-β1 and cell proliferation since TGF-β1 induces a rapid activation of ADAM-17 leading in turn to EGFR signalling [138]. In activated hepatic stellate cells, TGF-βl induces ADAM-12 expression which might also participate in tumour progression [139].…”
Section: Liver Carcinomamentioning
confidence: 99%